Hyperglycemia Promotes TMPRSS2-ERG Gene Fusion in Prostate Cancer Cells via Upregulating Insulin-Like Growth Factor-Binding Protein-2 - Holly, Jeff M. P.; Broadhurst, Jessica; Mansor, Rehanna; Bahl, Amit; Perks, Claire M. (Frontiers in Endocrinology, 2017)
Background: epidemiologic evidence shows that obesity is associated with a greater risk of aggressive prostate cancer and prostate cancer-specific mortality and this is observed mainly in men with the TMPRSS2-ERG gene fusion. Obesity is often associated with co-morbid conditions such as type 2 diabetes and hyperglycaemia: we investigated whether some of the exposures associated with disturbed metabolism can also affect the frequency of this gene fusion. Methods: fusion was induced in LNCaP prostate cancer cells in normal or high levels of glucose, with or without insulin-like growth factor binding protein-2 (IGFBP-2) silenced or the presence of IGF-I, insulin or epidermal growth factor (EGF). RNA was extracted for analysis by nested PCR. Abundance of IGFBP-2, H2AX, DNA-dependent protein kinase catalytic subunit (DNAPKcs) and β-actin were analysed by Western immunoblotting. Results: our data suggests that hyperglycaemia-induced IGFBP-2 increased the frequency of the gene fusion that was accompanied by decreased levels of DNAPKcs implying that they were mediated by alterations in the rate of repair of double strand breaks. In contrast insulin, IGF-I and EGF all decreased gene fusion events. Conclusions: these novel observations may represent a further mechanism by which obesity can exert an effect aggravating prostate cancer progression.